UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAM MASALAH MATEMATIKA MELALUI PENERAPAN SCAFFOLDING PADA SISWA KELAS VIII SEMESTER GENAP SMP NEGERI 1 BANDAR LAMPUNG TAHUN PELAJARAN 2016/2017 - Jumyati, Jumyati (LPPM STKIP PGRI Bandar Lampung, 2019)
This study uses the Classroom Action Research method which aims to improve students' mathematical problem solving skills by applying Scaffolding. The subject of this study was the tenth grade students of SMPN 1 Bandar Lampung, totaling 12 students. Data collection is done by observation, interviews, tests and documentation. Data processing is done by qualitative descriptive analysis. The data obtained is an increase in the first cycle to the second cycle of 8.75%, then the increase in the second cycle to the third cycle is 10.00%, and the increase in cycle I to the third cycle is 18.75%. So it can be concluded that an increase in students' mathematical problem solving skills can be done by applying Scaffolding.